Summation of partial wave expansions in the scattering by long range potentials. II. Numerical applications - Garibotti, C. R.; Grinstein, F. F. (AIP Publishing, 1978)
The numerical application of a sequence transformation method proposed in a previous work is considered for the calculation of differential cross-sections corresponding to processes where long range interactions are important. The advantages of the approach, as a summation algorithm for the partial wave expansion of the scattering amplitude, are shown for the cases of scattering by the Lennard-Jones, repulsive inverse square, and Coulombic potentials, and for the scattering of electrons by helium in the intermediate energy range. Furthermore, the method proves to be a regularizing procedure for divergent and oscillating partial wave expansions. © 1979 American Institute of Physics.